2009
DOI: 10.1021/ie9002552
|View full text |Cite
|
Sign up to set email alerts
|

Multiplicity Behavior of Trickle Flow Liquid−Solid Mass Transfer

Abstract: Dissolution as well as electrochemical techniques confirmed the existence of multiplicity. The commonly accepted upper multiplicity branch (achieved by Kan liquid prewetting) outperformed the lower branch (achieved by Levec prewetting) by as much as 1.6 times in Sherwood numbers. Although similar trends were observed for the two measurement techniques, the dissolution measurements were significantly lower than the electrochemical measurements. It was further shown that the multiplicity behavior of liquid-solid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…Although the instantaneous mass transfer coefficients in this subfigure are not affected by wetting efficiency, a marked difference between Levec and extensively pre‐wetted beds still persist. This finding is in direct agreement with the results from Joubert and Nicol41 who observed slower liquid–solid mass transfer in a Levec prewetted bed than in an extensively prewetted bed, even though the interstitial velocity is higher (lower liquid holdup). This suggests that the difference in flow structure between the Levec and extensively prewetted beds24, 42–45 has a severe impact on the liquid–solid mass transfer characteristics.…”
Section: Resultssupporting
confidence: 92%
“…Although the instantaneous mass transfer coefficients in this subfigure are not affected by wetting efficiency, a marked difference between Levec and extensively pre‐wetted beds still persist. This finding is in direct agreement with the results from Joubert and Nicol41 who observed slower liquid–solid mass transfer in a Levec prewetted bed than in an extensively prewetted bed, even though the interstitial velocity is higher (lower liquid holdup). This suggests that the difference in flow structure between the Levec and extensively prewetted beds24, 42–45 has a severe impact on the liquid–solid mass transfer characteristics.…”
Section: Resultssupporting
confidence: 92%
“…Thus, a "co-current-flow" configuration with the cathode and anode stacked at different axial positions [26,43,44] between polyurethane foam blocks was chosen. To minimize the ohmic potential drop, the electrodes were installed above and below one polyurethane foam block 100 mm in height.…”
Section: Experimental Set-up and Conditionsmentioning
confidence: 99%
“…The influence of the initial distribution on the wetting fraction was investigated with three different liquid distributors: single-point and multi-point distributors, and a spray nozzle. Oxidation occurred at the anode (A), while reduction (reverse reaction) occurred at the cathode (B): Thus, a "co-current-flow" configuration with the cathode and anode stacked at different axial positions [26,43,44] between polyurethane foam blocks was chosen. To minimize the ohmic potential drop, the electrodes were installed above and below one polyurethane foam block 100 mm in height.…”
Section: Experimental Set-up and Conditionsmentioning
confidence: 99%
“…As such, the experimental results of Babu and coworkers ) cannot be included due to the fact that conditions for individual data points have not been reported. It is worth commenting that packing procedure (Zou and Yu 1995) and start-up operation (Loudon et al 2006, Joubert andNicol 2009) may also influence thermal conductivity values, but no systematic studies were found in the literature to undertake a reliable analysis.…”
Section: Analysis Of the Available Experimental Information And Corrementioning
confidence: 99%